Evaluating bowel preparation tolerability in IBD: a phase 3 post-hoc comparison of mannitol and PEG-ASC - Tontini, Gian Eugenio; Rimondi, Alessandro; Caprioli, Flavio; Aldinio, Giovanni; Pastorelli, Luca; Radaelli, Franco; Spada, Cristiano; Vecchi, Maurizio (Frontiers in Gastroenterology, 2025)
Bowel preparation is a significant challenge for patients undergoing colonoscopy, especially in Inflammatory Bowel Disease (IBD) patients. Oral mannitol (OM), an ultra-low-volume, single-dose osmotic laxative with a sweet taste, could improve patient tolerability. We performed a post-hoc analysis of the phase 3, multicentre, randomized, endoscopist-blinded SATISFACTION trial to compare same-day OM versus standard split-dose 2L polyethylene glycol plus ascorbate (PEG-ASC) for bowel preparation in IBD patients. Fifty-five IBD patients (24 OM, 31 PEG-ASC) were assessed for bowel cleansing efficacy, endoscopic outcomes, safety, and patient satisfaction. OM demonstrated superior tolerability, including ease of use (88% vs. 71%), taste satisfaction (75% vs. 6%), and willingness to reuse (96% vs. 71%). OM also reduced intake duration (32 vs. 107 minutes) and time to evacuation (57 vs. 91 minutes), with comparable efficacy, cleansing quality, and safety. In conclusion, same-day OM preparation enhances satisfaction and adherence in IBD patients, offering a safe, effective alternative to standard protocols.